2002
DOI: 10.1193/1.1464535
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Site Response in Anchorage, Alaska, on the Basis of Spectral Ratio Methods

Abstract: This paper deals with the site response (SR) in the Anchorage basin in south-central Alaska. The investigation is based on the analysis of seismograms of 114 earthquakes recorded by 22 weak-motion stations and 46 earthquakes recorded by 19 strong-motion stations in the study area. We have computed SR for 41 sites, using standard spectral ratio and horizontal-to-vertical spectral ratio methods in the frequency range from 0.5 to 11 Hz. Based on these results, we have calculated band-average site response values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 17 publications
3
34
0
Order By: Relevance
“…The results are shown in Figures 3-7 for five representative sites located in site classes C, C/D, and D. These site classes were estimated by Martirosyan et al (2002) based on the results of an average of 30 m shear-wave velocity data of the Anchorage basin (Dutta et al, 2000). Of the five sites, one site (K203) is located in the area of site class C on the eastern side of the basin.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results are shown in Figures 3-7 for five representative sites located in site classes C, C/D, and D. These site classes were estimated by Martirosyan et al (2002) based on the results of an average of 30 m shear-wave velocity data of the Anchorage basin (Dutta et al, 2000). Of the five sites, one site (K203) is located in the area of site class C on the eastern side of the basin.…”
Section: Resultsmentioning
confidence: 99%
“…Because the observed SRf for the Anchorage basin were computed as previously mentioned with respect to the rock sites (An01 and K216) located on the metamorphic terrane of the Chugach Mountains in the eastern part of the basin, we used a 1D-layered Earth model of this site to compute T ref f. Martirosyan et al (2002) has shown that the rock sites of the Anchorage basin do not have unit site response above 7.0 Hz, as these sites overlay weathered rocks due to constant freezing and thawing in the area. Recent borehole drilling data at the rock site indicate that a 4 m thick weathered rock overlays the hard rock.…”
Section: Forward Modeling and Model Parameterizationmentioning
confidence: 99%
See 3 more Smart Citations